شرح الأربعين النبوية = Commentary on the Forty Hadith of Imam Nawawi: the timeless Prophetic gems of guidance and wisdom - Badi, Jamal Ahmed Bashier (Islamic Learning Foundation (ILF), 2016)
The commentary is a humble effort made to benefit the layman as well as intellectuals from different disciplines with little background in Islamic Studies. In addition, this commentary also offers discussions on related contemporary issues pertaining to various concepts mentioned in the Forty Ahadith collected by Imam Nawawi.